Urban sprawl shape description / N. Laila A. Ghani, Siti Z.Z. Abidin and N. Elaiza A. Khalid - A. Ghani, N. Laila; Z. Abidin, Siti Z.; A. Khalid, N. Elaiza (Penerbit UiTM, 2014)
Urban sprawl is the out-of-control growth of urban area as a result of improper urbanization plan. Literatures have characterized various forms of urban sprawl that includes low-density and leapfrog sprawl. The forms of sprawl can be modelled via satellite remote sensing images. This research is mainly about classifying the forms of urban sprawl by using pixel-based approach and representing the sprawl shape using centroid distance Fourier descriptor. The datasets are in the form of Landsat Thematic Mapper(TM) images of Klang Valley, Malaysia, at spatial resolution of 30 meters where each pixel in the image represents the area of 900 square meters on the ground. Results obtained show that the Fourier descriptor graph representation of low-density sprawl is denser than leapfrog sprawl. Due to the rapid urbanization process in Malaysia, it is important to identify the sprawling pattern for a better decision making in planning potential land area to be developed.